Hydroxytyrosyl Oleate: Improved Extraction Procedure from Olive Oil and By-Products, and In Vitro Antioxidant and Skin Regenerative Properties - Cinzia Benincasa; Chiara La Torre; Pierluigi Plastina; Alessia Fazio; Enzo Perri; Maria Cristina Caroleo; Luca Gallelli; Roberto Cannataro; Erika Cione (MDPI AG, 2019)
Recently, we identified hydroxytyrosyl oleate (HtyOle) in the by-products of olive oil, pomace and olive mill waste water (OMWW). Herein, we report that HtyOle is more accurately quantified by extracting the phenolic fraction from both matrices by using aqueous methanol (80%). By applying this method, HtyOle was also detected in extra virgin olive oil (EVOO). Since olive oil is used in the preparation of many cosmetic formulations, we explored the antioxidant capacity of HtyOle in human keratinocytes. Formation of reactive oxygen species (ROS) and malondialdehyde (MDA), as well as activity of Glutathione-S-transferase (GST) and superoxide dismutase (SOD) were decreased by HtyOle. In addition to that, microRNAs (miRs) involved in both redox status balance and skin regeneration potential were also tested. The following miRs, hsa-miR-21 and hsa-miR-29a, were increased while has-miR-34a was not affected by HtyOle.